Analisis Efektivitas Pengawasan Pajak Air Tanah Dalam Meningkatkan Pendapatan Daerah Pada Suku Badan Pendapatan Daerah Jakarta Timur Tahun 2021-2023 - Nahaso Laia; Jiwa Pribadi (Jurnal Ilmu Administrasi Publik, 2025)
The purpose of this study is to determine the effectiveness of the groundwater tax increase implemented by the East Jakarta Regional Revenue Agency (Subangda Daerah Pendapatan Daerah Jakarta) to increase local revenue. A key consideration in determining the effectiveness of groundwater tax is understanding the efforts employed to increase groundwater tax at the East Jakarta Sub-District Revenue Agency (Subangda Daerah Pendapatan Daerah Jakarta). Understanding the efforts implemented will facilitate the increase in local revenue. To obtain data and information, this study utilized interviews and observation as data collection methods. The author obtained primary data from respondents, namely employees of the East Jakarta Sub- District Revenue Agency (Subangda Daerah Daerah Jakarta), while secondary data was obtained from the library by searching for books related to taxation.Our tax law adheres to a self-assessment system, where taxpayers are entrusted with calculating and determining the amount of income owed and then reporting it to the tax counseling and consultation office after the end of the tax year. Keywords Local Reveneu, Groundwater Tax Sector